Overweight and High Sodium Intake Increased Risk of Hypertension among Adolescents: A Case-Control Study in Urban Setting - Rifka Annisa Aura Nuradina; Widya Asih Lestari; Imas Arumsari (Amerta Nutrition, 2023)
Background: Hypertension is the leading risk factor for cardiovascular disease development. Although hypertension in adults and the elderly is more common, adolescent hypertension has increased in the past two decades. Hypertension at an early age affects cognitive performance and increases the risk of cardiovascular diseases and premature death in the future. The risk factors of hypertension are often related to urban populations' unhealthy lifestyles.